Analisis Pemahaman Siswa Terhadap Materi Bangun Ruang Sisi Datar Pada Siswa/i Kelas IV SDN 04 Pulau Punjung - 73bi- vebriyanti25 (Jurnal Dharma PGSD, 2025)
This study aims to determine students' understanding of the material on flat-sided spatial figures in grade IV students of SDN 04 Pulau Punjung. To achieve the research objectives, the researcher used three stages, namely the planning stage, implementation and evaluation. This study uses a quantitative research method. The first stage carried out is the planning stage, in the planning stage the researcher prepares an observation permit, the media used, student worksheets and an assessment questionnaire on the material on the concept of flat-sided spatial figures. The second stage is the implementation stage, at this stage the researcher explains the material on flat-filled spatial figures and gives a worksheet to students. The last stage is evaluation, at this stage the researcher is carrying out teaching activities, other researchers provide assessments using the Flat-sided spatial figure questionnaire. Based on the results of the study, the average value of students' understanding of the material on flat-sided spatial figures in grade IV students of SDN 04 Pulau Punjung was obtained with a percentage of 69%. So, it can be concluded that students' understanding of the material on flat-sided spatial figures in grade IV students of SDN 04 Pulau Punjung is included in the good category.